High-fat overfeeding impairs peripheral glucose metabolism and muscle microvascular eNOS Ser1177 phosphorylation - Parry, S; Turner, M; Woods, R; James, L; Ferguson, R; Cocks, M; Whytock, K; Strauss, J; Shepherd, S; Wagenmakers, A; Van Hall, G; Hulston, C (Oxford University Press, 2019)
Context The mechanisms responsible for dietary fat-induced insulin resistance of skeletal muscle and its microvasculature are only partially understood. Objective To determine the impact of high-fat overfeeding on postprandial glucose fluxes, muscle insulin signaling, and muscle microvascular eNOS content and activation. Design Fifteen non-obese volunteers consumed a high-fat (64%) high-energy (+47%) diet for 7 days. Experiments were performed before and after the diet. Stable isotope tracers were used to determine glucose fluxes in response to carbohydrate plus protein ingestion. Muscle insulin signaling was determined as well as the content and activation state of muscle microvascular eNOS. Results High-fat overfeeding impaired postprandial glycemic control as demonstrated by higher concentrations of glucose (+11%; P = 0.004) and insulin (+19%; P = 0.035). Carbohydrate plus protein ingestion suppressed endogenous glucose production to a similar extent before and after the diet. Conversely, high-fat overfeeding reduced whole body glucose clearance (-16%; P = 0.021) and peripheral insulin sensitivity (-26%; P = 0.006). This occurred despite only minor alterations in skeletal muscle insulin signaling. High-fat overfeeding reduced eNOS content in terminal arterioles (P = 0.017) and abolished the increase in eNOS Ser1177 phosphorylation that was seen after carbohydrate plus protein ingestion. Conclusion High-fat overfeeding impaired whole-body glycemic control due to reduced glucose clearance, not elevated endogenous glucose production. The finding that high-fat overfeeding abolished insulin-mediated eNOS Ser1177 phosphorylation in the terminal arterioles suggests that impairments in the vasodilatory capacity of the skeletal muscle microvasculature may contribute to early dietary fat-induced impairments in glycemic control.